Individual and Organizational Impacts of Flexible Work: A Study of Women Workers in North America - Marija TRESOGLAVIC; Ron FISHER (Journal of Human Resource Management)
Purpose – In this research we investigated how North American women experienced flexible work along with the benefits and challenges associated with such modes of work. Aim – The study aimed to understand the impacts of hybrid/remote work environments and determine why women working in North America perceived them to be important. It also aimed to investigate the impact of a forced return to the physical workplace. Design/methodology/approach – The study employed a qualitative approach with data collected by interviewing 14 women selected from a social network. A constant comparison approach was used to analyze data thematically and to identify meta-themes. Findings – Women participants regarded work-life balance, flexibility and a trusting work relationship as benefits associated with flexible work. However, they expressed feelings of alienation leading to an intention to leave, resulting mainly from a loss of control, if forced to return to a wholly in-workplace mode of work. For organizations the findings suggest negative outcomes, which include employees leaving prematurely, lack of trust, alienative commitment, and perceptions of presenteeism. Limitations of the study – As with all qualitative research the finding are not generalizable. However, this does not detract from the value of the findings. Originality/value – The study extended previous research about women’s work/life balance, loss of control and turnover associated with flexible work modes. It also identified the presence of feelings of alienation associated with a perceived lack of control if women were forced to return to the physical workplace. Alienation can lead to alienative commitment, a powerful negative organizational force that often remains undetected and leads to dysfunctional outcomes.